Fungsi Kesenian Ubrug Mang Cantel Bagi Masyarakat Kampung Prisen Kecamatan Walantaka Kota Serang Banten - Uyi Lasmana; Alis Triena Permanasari; Giri Mustika Roekmana (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2022)
ABSTRACT.Ubrug art is a traditional theater art that has elements of jokes, jokes or commonly referred to as genre comedy.This research aims to describe the function of ubrug traditional theater art for the community.The source of this research data is Ubrug Mang Cantel workshop located in prisen village, Walantaka district, Serang Banten City.The theory used in research is function theory and cultural studies.The method used is a descriptive qualitate method. The collection of research data is conducted with interview techniques, direct observation, documentation and literature studies.From the results of the study found several Functions of Art Ubrug Mang Cantel for the people of Kampung Prisen including as a medium of entertainment and spectacle, Ubrug as an economic media for the perpetrators, as a medium of defense of The Javanese language Serang and Sunda Banten, as a medium of moral planting for and as a media of cultural defense banten.Kata kunci : fungsi, ubrug, teater rakyat banten.